Comparison of treatment costs for primary localized prostate cancer in Austria and Vienna: an economic analysis - Moll, Matthias; Goldner, Gregor (Frontiers in Public Health, 2023)
Background Prostate cancer is the most common cancer in men. Several efficient treatments are available for primary prostate cancer, but an economic comparison of these modalities has not been done in Austria. Objective and setting The current study provides an economic comparison of radiotherapy and surgery for prostate cancer in Vienna and Austria. Methods We analyzed the catalog of medical services of the Austrian Federal Ministry of Social Affairs, Health, Care and Consumer Protection and present the treatment costs for the public health sector with an LKF-point value and monetary value in 2022. Results External beam radiotherapy, especially ultrahypofractionated, is the least costly treatment modality for low-risk prostate cancer, with costs of 2,492 € per treatment. For intermediate-risk prostate cancer, differences between moderate hypofractionation and brachytherapy are small, with costs of 4,638–5,140 €. In a high-risk setting, differences between radical prostatectomy and radiotherapy with androgen deprivation therapy are small (7,087 € vs. 7474.06 €). Conclusion From a purely financial point of view, treatment of low- and intermediate-risk prostate cancer in Vienna and Austria should consist of radiotherapy as long as the current catalog of services is up to date. For high-risk prostate cancer, no major difference was found.